Novel Two-Dimensional Carbon–Chromium Nitride-Based Composite as an Electrocatalyst for Oxygen Reduction Reaction - Khan, Karim; Tareen, Ayesha Khan; Aslam, Muhammad; Khan, Qasim; Khan, Sayed Ali; Khan, Qudrat Ullah; Saleemi, Awais Siddique; Wang, Renheng; Zhang, Yupeng; Guo, Zhongyi; Zhang, Han; Ouyang, Zhengbiao (Frontiers in Chemistry, 2019)
For future pollution-free renewable energy production, platinum group metal (PGM)-free electrocatalysts are highly required for oxygen reduction reaction (ORR) to avoid all possible Fenton reactions and to make fuel cell more economical. Therefore, in this study, to overcome traditional electrocatalyst limitations, we applied facile method to synthesize robust mesoporous CrN-reduced graphene oxide (rGO) nanocomposite with MnO (thereafter, Cr/rGO composite with MnO) as an electrocatalyst by efficient one-step sol-gel method by ammonolysis at 900°C for 9 h. Synthesized porous structures of Cr/rGO nanocomposite with MnO have the highest estimated surface area of 379 m2·g−1, higher than that of the carbon black (216 m2·gcat-1) support, and almost uniform pore size distribution of about 4 nm. The Cr/rGO nanocomposites with MnO exhibit enhanced electrocatalytic ORR properties with estimated high half-wave potential of 0.89 V vs. the reversible hydrogen electrode (RHE) and current density of 5.90 mA·cm−2, compared with that of benchmark 20% Pt/C electrode (0.84 V, 5.50 mA·cm−2), with noticeable methanol tolerance and significantly enhanced stability in alkaline media. Hence, the Cr/rGO nanocomposites with MnO showed superior performance to 20 wt.% Pt/C; their half-wave potentials were 50 mV high, and the limiting current density was 0.40 mA·cm−2 high. In alkaline anion exchange membrane fuel cell (AAEMFC) setup, this cell delivers a power density of 309 mW·cm−2 for Cr/rGO nanocomposite with MnO, demonstrating its potential use for energy conversion applications. The nanosized Cr/rGO metallic crystalline nanocomposites with MnO gave a large active surface area owing to the presence of rGO, which also has an effect on the charge distribution and electronic states. Hence, it may be the reason that Cr/rGO nanocomposites with MnO, acting as more active and more stable catalytic materials, boosted the electrocatalytic properties. The synergistic consequence in nanosized Cr/rGO composite with MnO imparts the materials' high electron mobility and thus robust ORR activity in 0.1 M of KOH solution. This potential method is highly efficient for synthesis of large-scale, non-noble-metal-based electrocatalytic (NNME) materials (i.e., Cr/rGO nanocomposite with MnO) on the gram level and is efficient in preparing novel, low-cost, and more stable non-PGM catalysts for fuel cells.